Fluorinated Glycopolymers as Reduction-responsive 19F MRI Agents for Targeted Imaging of Cancer - Fu, Changkui; Tang, Joyce; Pye, Aidan; Liu, Tianqing; Zhang, Cheng; Tan, Xiao; Han, Felicity; Peng, Hui; Whittaker, Andrew K (Biomacromolecules, 2019)
Imaging agents that can be targeted to specific diseases and respond to the microenvironment of the diseased tissue are of considerable interest due to their potential in diagnosing and managing diseases. Here we report a new class of branched fluorinated glycopolymers as 19F MRI contrast agents that respond to a reductive environment, for targeted imaging of cancer. The fluorinated glycopolymers can be readily prepared by a one-pot RAFT polymerization of glucose- and fluorine-containing monomers in the presence of a disulfide-containing cross-linking monomer. The incorporation of glucose units along the polymer chain enables these fluorinated glycopolymers to effectively target cancer cells due to interactions with the overexpressed sugar transporters present on the cell surface. In addition, the polymers exhibit an enhanced 19F MRI signal in response to a reductive environment, one of the unique hallmarks of many cancer cells, demonstrating their potential as promising candidates for targeted imaging of cancer.